全髋关节置换术治疗脊柱骨骺发育不良患者Tönnis 3级髋关节骨关节炎的早期疗效 (Beijing Da Xue Xue Bao Yi Xue Ban, 2021)
OBJECTIVE: Severe hip osteoarthritis, caused by bone or joint maldevelopment, biomechanical transformation and previous surgical intervention, is inclusively existed in spondyloepiphyseal dysplasia (SED). To investigate and discuss the short-term efficacy and possible effects of total hip arthroplasty in the treatment of Tönnis grade 3 hip osteoarthritis in patients with SED. METHODS: From January 2017 to June 2019, 374 patients with hip osteoarthritis were involved for total hip arthroplasty conducted by senior professional surgeons, of whom 9 patients (6 males and 3 females) with 12 hip osteoarthritis secondary to the SED met the inclusive and exclusive criteria and received the above-mentioned hip operation. The short-term outcomes were observed. RESULTS: All the patients were implanted with Johnson & Johnson ceramic on ceramic cementless hip prostheses within the arthroplasty. They were followed up for an average period of 20 months. Except for one muscular calf vein thrombosis case, no complications, such as aseptic loosening, joint dislocation, fracture, neurovascular injury, deep vein thrombosis and infection were observed in all the 9 patients. Before the surgery, the average Harris hip score was 35.55, while the average of the Western Ontario and McMaster Universities osteoarthritis index (WOMAC) was 56.56. The level of quality of life indicated by SF-12 score was 41.56 on average. The mean pre-operation visual analogue scale (VAS) was 7.44. At the last follow-up, the average Harris hip score increased to 89.56, whereas the average WOMAC declined to 41.11. Compared with the baseline point, the average SF-12 score went up to 56.33. Dramatic drop of the mean VAS value to 2.67 was also observed at the last follow-up. In addition, post-operative increase of several pelvic-related parameters including pelvic incidence, pelvic tilt and sacral slope could be observed in the SED patients. The average measured pelvic incidence, pelvic tilt and sacral slope were 68.95°±4.60°, 52.75°±1.06° and 17.45°±1.77° before operation, respectively; whilst the mean value of these specific parameters increased to 76.98°±5.12°, 60.51°±4.35° and 18.10°±2.02°, respectively. The even leg lengths of the lower extremities were obtained after total hip arthroplasty. CONCLUSION: Total hip arthroplasty is satisfactory in the short-term pain relieve and function recovery for the management of Tönnis grade 3 hip osteoarthritis secondary to the SED.